E-GOVERNMENT AS A COMPONENT OF PUBLIC SECTOR GOVERNANCE TRANSFORMATION - Fisenko, Nataliya (Theory and Practice of Public Administration, 2019)
The changes, that take place in the information society, have also affected the activities of public authorities, which have faced serious challenges related to the need to rebuild their relations with the inhabitants of territories, who not only clearly understand their information needs but also demand direct involvement in solution of pressing issues of social and economic development.The most effective form of interaction of government with citizens in the world is e-government system.Therefore, defining the model of e-government implementation is a difficult and multifaceted issue, compounded by the variety of problems and obstacles that are individual in each country. However, it is common for all countries to understand the need for e-government in terms of improving the quality and convenience of user / citizen / public services. Thus, the use of ICT and the development of e-governance should not be regarded as an end in itself.At the same time, it is clear that the competitive telecommunications market, as well as the professional environment that promotes e-governance, will allow it to become an accessible channel for interaction between public authorities, citizens and businesses. At the same time, it is necessary to create the legal, organizational and technical conditions that will give this interaction the legitimacy and guarantees necessary to secure electronic transactions and data exchange. In cases where telecommunications infrastructure is already available or cheaper as a result of competition, e-government programs quickly gain support and usually lead to success.